Primary Hyperparathyroidism: Clinical, Biochemical, and Radio-Pathological Profiles of 804 Patients – A Retrospective Study from South India - Dhalapathy Sadacharan; Mano Z. Mathews; Anjali Sathya; Shanmugasundar Gopal; Sruti Chandrasekaran; Sivasubramaniam Murthy; Vijaya B. Reddy; Jayashree Gopal; Muthukumaran Jeyapaul; Sakthivel Sivasubramanian; Vignesh Gopalakrishnan; Bharath Ramji; et al. (Indian Journal of Endocrinology and Metabolism, 2025)
Introduction: Primary hyperparathyroidism (PHPT) is a common endocrine disorder with variable clinical presentation. We intend to describe the clinical, biochemical, and radio-pathological profiles of PHPT patients managed over 13 years from South India. Methods: We analysed all patients who underwent evaluation and surgery for PHPT from July 2011 to April 2024. Results: A total of 862 PHPT patients underwent parathyroidectomy, with female preponderance (61.2%). Analysis was done on 804 patients (>20 years of age) excluding adolescent and paediatric age groups. The mean age was 43.8 years. The presentation in decreasing order of frequency was weakness and fatigue (84.2%); bone pain (35%); renal disease (20.8%) in the form of nephrolithiasis, nephrocalcinosis, or renal dysfunction; and neuropsychiatric manifestations (23.8%). Pathological fractures were observed in 4.5%, hypercalcaemic crisis in 2.6% of patients, and 1% had MEN I (Multiple Endocrine Neoplasia) syndrome. The mean albumin adjusted serum calcium level was 12.3 ± 1.01 mg/dl, and the median serum PTH level was 338 (80–3864) pg/ml. The sensitivity of the ultrasound neck and 99mTc Sestamibi scan was 97.5% and 98.3%, respectively, with a concordance of 93.4%. 25% underwent bilateral neck exploration and parathyroidectomy. Lesions were ectopic in 20 (2.4%) patients. The mean parathyroid gland weight was 1.45 ± 0.75 g. Histopathology revealed parathyroid adenoma (93.5%), parathyroid hyperplasia (1.6%), and parathyroid carcinoma (2.2%). The cure rate was 99.3%, while three patients had persistent disease. Hungry bone syndrome was observed in 12.1%. Conclusion: There is a changing trend in the clinical and biochemical profiles of PHPT patients in India to a milder form of the disease. The incidence of parathyroid carcinoma was slightly higher compared to a few other centres in India.